2012
DOI: 10.1038/ncomms1715
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-rapid access to words in the brain

Abstract: Rapid information processing in the human brain is vital to survival in a highly dynamic environment. The key tool humans use to exchange information is spoken language, but the exact speed of the neuronal mechanisms underpinning speech comprehension is still unknown. Here we investigate the time course of neuro-lexical processing by analysing neuromagnetic brain activity elicited in response to psycholinguistically and acoustically matched groups of words and pseudowords. We show an ultra-early dissociation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
121
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(142 citation statements)
references
References 50 publications
15
121
2
Order By: Relevance
“…However, most recent investigations suggested that the earliest brain reflections of lexical access can be seen much earlier, already at 50-80 ms (23). This earliness, in turn, may indicate that the speed of language processing in the brain is faster than believed previously and that even the 150-to 200-ms activations may therefore be late and possibly even secondary.…”
Section: Significancementioning
confidence: 89%
“…However, most recent investigations suggested that the earliest brain reflections of lexical access can be seen much earlier, already at 50-80 ms (23). This earliness, in turn, may indicate that the speed of language processing in the brain is faster than believed previously and that even the 150-to 200-ms activations may therefore be late and possibly even secondary.…”
Section: Significancementioning
confidence: 89%
“…They wanted to find out about the point in time when the acoustic information allows word recognition. Results showed that this crucial point occurs 50-80 ms after presentation (McGregor et al, 2012). In a word reading task that compared different semantic word classes with similar physical appearance by using textual characters (Chinese), electrical brain activation differed significantly for each semantic word class.…”
Section: Realistic Time Frames For Turn-end-detectionmentioning
confidence: 90%
“…Müller and Kutas (1996), for example, showed that the initial 100-120 ms of words already provide enough information in order to decide whether a sound is the beginning of a noun or a name. In another study McGregor et al (2012) investigated the crucial point of word recognition in spoken words versus pseudowords. They wanted to find out about the point in time when the acoustic information allows word recognition.…”
Section: Realistic Time Frames For Turn-end-detectionmentioning
confidence: 99%
“…MacGregor et al [20] and Visser et al [21] state that lexicalsemantic categorization is necessary to interpret words and cannot be performed for invented words. Given the Google hypothesis 'Musa red pyramid for sale spec', our system "does not know" words like 'Musa', 'sale' or 'spec', as they are not contained in the training data.…”
Section: Discussionmentioning
confidence: 99%